Health models and response capacity to epidemiological risks: Towards a universality in terms of access and free services - Pérez Gázquez, Isabel María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The health emergency caused by covid-19 has highlighted the importance of preventive measures to guarantee the health of the population. Also, that the universality of the health system, with free access for all people to these preventive activities, affects both individual and collective health, becoming an essential tool for carrying out adequate epidemiological surveillance. Therefore, the objective of this work is to expose the relationship between the breadth of this ownership and the effectiveness of these preventive public health measures against infectious and contagious diseases.